A PKI-based multi-channel unified identity authentication method for energy information system - Yang TANG; Yiying ZHANG; Yeshen HE; Cong WANG; Ming LEI (Dianxin kexue)
There are problems of poor user experience,inconsistent management,and potential security risks in energy information system.It is urgent to study the issue of unified identity authentication between various electronic channels from the source to achieve unified management of multiple electronic service channels and service supervision of various electronic channels.A multi-dimensional electronic channel unified authentication method based on PKI certification was proposed for energy information system.Users could directly access each application system through the proposed method and perform fast and secure switching between application systems without multiple authentication processes.The approach provided users with the convenience and security of engaging in complex business management activities.